Verso una pedagogia innovativa della lettura: codici testuali e codici digitali - Carioli, Stefania (Studi sulla Formazione/Open Journal of Education, 2015)
This paper presents a reflection on the subject of traditional reading and digital reading, and focuses on the pedagogical implications when moving from print to a digital reading environment. It stresses out the differences between the digital reading of the texts, such as the e-books, and the digital reading on the Internet. Based on the acquisitions coming mainly from the neuroscientific scope, it suggests the complexity of online reading is not favorable to the readers who are at the beginning of their path of literacy. The paper notes that for the novice read- ers is more appropriate to read both on printed page and on digital content that maintain largely the printing features - such as stability, linearity, the fulfillment of the content. These features attract the full attention of the reader and encour-age the development of cognitive processes at the base of a deep reading. These processes must be strengthened expecially at the beginning of the reading learning process. The online reading can be addressed later, using metacognitive techniques and self-regulated strategies that accustom the reader to stop on a text and to monitor his/her comprehension, to resist a superficial reading, and to engage the research for a deeper meaning. The article emphasizes the importance of integrating the two forms of reading and to promote the best of both literacies.